GEJOLAK PASAR DAN BUDAYA SEBAGAI MODERASI PENGARUH ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR TERHADAP KINERJA PEMASARAN - Ayun Maduwinarti (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The objectives of this research were to examine and analyze: (1) the effect of entrepreneurial orientation toward marketing performance, (2) the effect of market orientation toward marketing performance, (3) the effects of market turbulence and culture on the strong/weak impact of entrepreneurial orientation toward marketing performance, (4) the effects of market turbulence and culture on the strong/weak impact of market orientation toward marketing performance. The populations of this study were all “Melati” hotels in East Java, as many as 463 hotels spread across cities/regencies in East Java. The sample units were the “Melati” hotels and the respondents were the owners/managers of “Melati” hotels, as many as 90 people. The samples were determined through two stages: the sample area was determined by using Judgment Sampling and the sample of hotels in each city/region which have been selected was defined by Proportional Area Random Sampling. The data analysis used was PLS (Partial least Square). The research result showed that entrepreneurial orientation did not have a significant effect on marketing performance. It was evident that market orientation was influential to marketing performance. The market turbulence as a moderating variable weakened the influence of entrepreneurial orientation and market orientation toward marketing performance. Culture is obviously a moderating effect on entrepreneurial orientation toward marketing performance. There was a coefficient of positive interaction, therefore, culture as the moderator strengthened the influence of entrepreneurial orientation toward marketing performance